Drying in the process industry - Land, C. M. van't, 1937- (Wiley, 2012)
"This book assists the process development engineer, the process engineer, and the plant engineer in selecting drying equipment. The criteria to be observed are discussed. The procedure concerning the selection of an industrial dryer always starts with the gathering of results of relevant laboratory measurements. The next step is carrying out small-scale tests, the results of which can be scaled up. Procedures for sizing equipment are also covered. Written by an author with over four decades in the process industries, this book brings an extensively practical approach for the engineer"--